EVOLUTION OF THE CONCEPT AND INSTRUMENTS OF DEOFFSHORIZATION OF THE RUSSIAN ECONOMY - A. Mikhaylin; Y. Grigoryeva (Вестник университета)
Offshore zones were widely used in the Russian economic practice that has led to contradictions between interests of business and the state. In the article tools and the directions of deoffshorization of the Russian economy at the present stage are considered and generalized.